Semantic and prosodic threat processing in trait anxiety: is repetitive thinking influencing responses?. Issue 1 (2nd January 2021) - Busch-Moreno, Simon; Tuomainen, Jyrki; Vinson, David
ABSTRACT: The present study attempts to identify how trait anxiety, measured as worry-level, affects the processing of threatening speech. Two experiments using dichotic listening tasks were implemented; where participants had to identify sentences that convey threat through three different information channels: prosody-only, semantic-only and both semantic and prosody (congruent threat). We expected different ear advantages (left or right) depending on task demands, information type, and worry level. We used a full Bayesian approach for statistical modelling and analysis. Main results indicate that as worry-level increases, participants' reaction times increase. We explain this effect by proposing a fourth stage, associated with goal-oriented deliberation, for a three-phasic multistep model of emotional language processing. Higher levels of trait anxiety could induce verbal repetitive thinking (i.e. worry and/or rumination), which might prolong the mentioned deliberation stages, thus slowing down responses.